Exome sequencing identifies predisposing and fusion gene in ganglioneuroma, ganglioneuroblastoma and neuroblastoma - Wei Wu; Weijue Xu; Jiangbin Liu; Jun Sun; Yimin Huang; Zhibao Lv (Mathematical Biosciences and Engineering, 2019)
This study intended to gain new insight into the genetic basis underlying ganglioneuroma (GN), ganglioneuroblastoma (GNB), and neuroblastoma (NB). Three fresh-frozen surgically resected tumor tissues (GN1, GNB1, and NB1) and matched blood samples (GN2, GNB2, and NB2) were respectively obtained from three pediatric patients with GN, GNB, and NB. After exome sequencing, we predicted the somatic single nucleotide variants (SNV) and insertion and deletion (InDel), and screened the predisposing genes. Finally, we detected and filtered the fusion gene using Fusionmap. Exome sequencing identified 815,985, and 884 somatic SNV, and 56, 43, and 34 InDel for GN, NB, and GNB respectively. Total 29, 19 and 37 predisposing genes were identified from GN, GNB and NB samples, such as PIK3CA (GN), MUC4 (GN), PML (NB), TFR2 (GNB), and MAX (GNB). Additionally, four common fusion genes, such as HOXD11-AGAP3 and SAMD1-CDC42EP5, were identified from three tumor samples. Moreover, SAMD1-CDC42EP5 was also a common fusion position in three blood samples. These previously unrecognized predisposing genes, such as PIK3CA, MUC4, PML, TFR2 and MAX, and fusion genes, like HOXD11-AGAP3, and SAMD1-CDC42EP5 may have the potential to impact the progression and development of neuroblastic tumors.